Uma contribuição para o estudo sobre o erro não amostral na pesquisa de mercado - Zanotta, Egydio Barbosa (2013)
The main objectiv of this study is to present a contribution to the non sampling error in the Marketing Research. To reach this goal we had ( by means of bibliografical research) to discover and typify the non sampling error which is present in a research project, assuming the presence of this error in each step of the process. Finally we tried to solve these problems by taking into account the more recents conquests of the knowledge in this area. It is important to emphasize that we included notes and theories originated from our own experience, stimulated by the opinion of the advisor of our thesis